Linking bacterial life-history strategies and diversity to litter decomposition dynamics in a dry-hot valley area - Yang, Tao; Shi, Chunjuan; Chang, Enfu; Zhou, Yun; Li, Pinrong; Liu, Qiang; Zhang, Xiqing; Pang, Jing (Frontiers in Microbiology, 2026)
Litter decomposition is a critical ecosystem process that influences nutrient cycling and carbon sequestration, yet the role of microbial communities, especially bacteria, in driving decomposition dynamics is not well understood, particularly in stress-prone ecosystems. This study examines the relationship between bacterial life-history strategies, community diversity, and litter chemical properties during the decomposition of six herbaceous plant species in a dry-hot valley ecosystem. Over a 493-day period, we monitored litter mass loss, chemical composition (C, N, P, lignin, cellulose) at five decomposition stages (T1_69–T5_493), and bacterial community shifts at three representative stages (T1_69, T3_271, and T5_493). Our results show that bacterial traits, including life-history strategies, explained a larger proportion of variance in litter decomposition rates compared to chemical properties. Litter mass loss followed a clear “fast–slow” temporal pattern, and species-specific exponential decay parameters (k) indicated interspecific differences in decomposition rates. Bacterial communities shifted significantly in diversity and composition, with oligotrophic bacteria becoming dominant in later stages. The abundance of bacterial groups was closely correlated with litter traits like lignin and cellulose, but not with nitrogen or phosphorus ratios. Random forest analysis identified key bacterial biomarkers, whose abundance varied across decomposition stages, and canonical correspondence analysis emphasized the role of litter quality gradients (particularly cellulose and lignin) in shaping bacterial community structure. These findings highlight the importance of integrating microbial strategies and litter chemistry to understand decomposition dynamics, especially in water-limited ecosystems.